Glucocorticoids induce amiloride-sensitive ion transport by pathways that are tissue-specific - Quesnell, Rebecca R. (Kansas State University, 2007)
The goal of this project was to define mechanisms responsible for Na+ transport in two hormonally-sensitive epithelium, the bovine mammary gland and porcine vas deferens. Glucocorticoid stimulation in these epithelia results in a significant increase in amiloride-sensitive ion transport, suggesting regulation of the epithelial Na+ channel, ENaC. ENaC has typically been described as a heteromultimeric ion channel with at least three different types of subunits, the most common being , β, and γ. Glucocorticoid-induced regulation of these subunits at the transcriptional level appears to be very different in the porcine vas deferens as compared to the bovine mammary gland. The aims of the study in mammary epithelium were to elucidate the mechanisms by which apical electrolytes and cytokines compromise barrier function in mammary epithelium. The long term goal is to better understand and manage the interaction between ionic composition of milk and breakdown of the gland epithelium that occurs during mastitis. Our results suggest a causal link between changes in milk electrical conductivity and epithelial barrier breakdown that has not been appreciated previously. Results will provide benefits to dairy farmers by characterizing steps that might prevent the development of mastitis or hasten recovery. The aims of the study using porcine vas deferens epithelial cells include determining the time course, concentration- and structure-dependency for regulation of amiloride-sensitive ion flux by corticosteroids. Corticosteroids caused a concentration-dependent increase in amiloride-sensitive Isc with a rank order of potency of dexamethasone>prednisolone>cortisol. Hill analysis indicates steep concentration dependency. The corticosteroid-induced, amiloride-sensitive current is Na+ absorption as indicated by radiotracer flux measurements. Studies employing selective antagonists (spironolactone, mifepristone) define glucocorticoid receptor mediation. These results suggest that vas deferens epithelia are exquisitely sensitive to corticosteroid exposure. Observed changes in epithelial function in response to corticosteroid exposure would rapidly and chronically affect the luminal environment to which sperm are exposed. Thus, physiological and pharmacological corticosteroid exposure is expected to affect male fertility.
Keywords: glucocorticoids; ENaC; bovine; porcine; mammary; reproduction; Biology, Animal Physiology (0433); Biology, Cell (0379); Biology, Veterinary Science (0778)